Elderly assisted living system - Lim, Jun Hong (2015)
As society moderns, Singapore will have a low birth rate which in turn leads to an ageing population. More people will need healthcare benefits and technology could help out to take care of the elderly, be it a device that allows self-monitoring of blood pressure, or setting up video cams around the room to monitor their movements should accidents happen. This project uses a Radio-Frequency Identification (RFID) transmit-only tag that operate on Impulse Radio Ultra Wideband(IR-UWB) technology. The hardware consists of the tag, four sensors and a locator box. By using the hardware, MATLAB and Time Difference of Arrival (TDOA) technique, the position of the tag can be shown on a computer display. The first part of this project aims to find out the standard deviation error of the tag in different parts of the room with all four sensors. The second part of this project is to carry out many testing of the tag at different gain, locations and orientations, using one sensor at a time to obtain the individual signal of each sensor, so as to obtain the characteristic of the tag and sensors. All the measurements in this experiment were conducted in Internet of Things (IoT) laboratory. Certain areas were not tested because it might cause obstructions to other students.